Governance for Human Security: Response to COVID-19 Pandemic in Morang District, Nepal - Karki, Netra Bahadur (Journal of APF Command and Staff College, 2021)
This study is focused to probe the impacts of COVID-19 pandemic and human security-oriented response in Nepal. Particularly Morang district is purposefully selected as the area of study. Qualitative meta-analysis and semi-structured telephone interview were the methods utilized for the qualitative data collection. The response mechanism adopted can be made further influential through minor adjustments as public always look forward to receiving extra effective responses during emergencies. Local levels have been doing their best with limited resources, where some are capable of mobilizing additional resources. Good practices relating to economic decision-making and implementation by all three levels of governments can amplify the vibes of responses posing positivity in the fighters at the frontline during the fight against non-traditional adversary such as COVID-19 pandemic.